A phase 1b study evaluating the safety and preliminary efficacy of berzosertib in combination with gemcitabine in patients with advanced non-small cell lung cancer. (January 2022) - Plummer, Ruth; Dean, Emma; Arkenau, Hendrik-Tobias; Redfern, Charles; Spira, Alexander I.; Melear, Jason M.; Chung, Ki Y.; Ferrer-Playan, Jordi; Goddemeier, Thomas; Locatelli, Giuseppe; Dong, Jennifer; Fleuranceau-Morel, Patricia; et al.
Highlights: Berzosertib plus gemcitabine was well tolerated in 38 patients with advanced NSCLC. Preliminary signs of clinical efficacy were observed. Response rate was numerically increased in patients with high TMB and LOH scores. Potential DDRi biomarkers should be investigated in genomically selected patients. Berzosertib plus chemotherapy is being investigated in other treatment settings. Abstract: Objectives: Berzosertib (formerly M6620, VX-970) is an intravenous, highly potent and selective, first-in-class ataxia telangiectasia and Rad3-related (ATR) protein kinase inhibitor. We assessed the safety, tolerability, preliminary efficacy, and pharmacokinetics (PK) of berzosertib plus gemcitabine in an expansion cohort of patients with advanced non-small cell lung cancer (NSCLC). The association of efficacy with TP53 status and other tumor markers was also explored. Materials and methods: Adult patients with advanced histologically confirmed NSCLC received berzosertib 210 mg/m 2 (days 2 and 9) and gemcitabine 1000 mg/m 2 (days 1 and 8) at the recommended phase 2 dose established in the dose escalation part of the study. Results: Thirty-eight patients received at least one dose of study treatment. The most common treatment-emergent adverse events were fatigue (55.3%), anemia (52.6%), and nausea (39.5%). Gemcitabine had no apparent effect on the PK of berzosertib. The objective response rate (ORR) was 10.5% (4/38, 90% confidence interval [CI]: 3.7–22.5%). In the exploratory analysis, the ORR was 30.0% (3/10, 90% CI: 9.0–61.0%) in patients with high loss of heterozygosity (LOH) and 11.0% (1/9, 90% CI: 1.0–43.0%) in patients with low LOH. The ORR was 33.0% (2/6, 90% CI: 6.0–73.0%) in patients with high tumor mutational burden (TMB), 12.5% (2/16, 90% CI: 2.0–34.0%) in patients with intermediate TMB, and 0% (0/3, 90% CI: 0.0–53.6%) in patients with low TMB. Conclusions: Berzosertib plus gemcitabine was well tolerated in patients with advanced, pre-treated NSCLC. Based on the observed clinical efficacy, future clinical trials should involve genomically selected patients.